2022
DOI: 10.3389/fphar.2021.792293
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Wild-type p53 Facilitates Bone Metastatic Function by Blocking the AIP4 Mediated Ligand-Induced Degradation of CXCR4

Abstract: Background: Management of patients with prostate cancer and bone metastatic disease remains a major clinical challenge. Loss or mutation of p53 has been identified to be involved in the tumor progression and metastasis. Nevertheless, direct evidence of a specific role for wild-type p53 (wt-p53) in bone metastasis and the mechanism by which this function is mediated in prostate cancer remain obscure.Methods: The expression and protein levels of wt-53, AIP4, and CXCR4 in prostate cancer cells and clinical specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…These findings may help with PCa diagnosis and the development of alternative therapeutics [ 205 ]. Moreover, Wt-p53 inhibited the migration of PCa cells to the bones by altering the activity of CXCR4 and CXCL12 in the interactions between tumor cells and the bone marrow microenvironment [ 206 ]. These results imply that wt-p53/CXCR4 axis targeting may be a promising therapeutic approach to control PCa bone metastases.…”
Section: Chemokines/cxcrs and Pcamentioning
confidence: 99%
“…These findings may help with PCa diagnosis and the development of alternative therapeutics [ 205 ]. Moreover, Wt-p53 inhibited the migration of PCa cells to the bones by altering the activity of CXCR4 and CXCL12 in the interactions between tumor cells and the bone marrow microenvironment [ 206 ]. These results imply that wt-p53/CXCR4 axis targeting may be a promising therapeutic approach to control PCa bone metastases.…”
Section: Chemokines/cxcrs and Pcamentioning
confidence: 99%
“…BioScience Trends Advance Publication P8 early prognostication of prostate cancer progression (32). Deletion of wild-type p53 promoted prostate cancer cells metastasis to bones by regulating the C-X-C chemokine receptor type 4/ C-X-C motif chemokine 12 (CXCR4/ CXCL12) activity (33). This suggested that elucidating the downstream mechanism of TP53 mutation would help us find a promising therapeutic strategy.…”
Section: Wwwbiosciencetrendscommentioning
confidence: 99%